Peningkatan Kemampuan Literasi Berpantun Siswa Kelas Vii.1 Smp Negeri 4 Kendari Melalui Model Pembelajaran Project Based Learning - Sukadir Kete; Nurhaeni Nurhaeni (Jurnal Sultra Elementary School, 2022)
This study aims to improve the reading and writing skills of pantun (traditional Indonesian poetry) among seventh-grade students (class VII-1) at SMP Negeri 4 Kendari through the implementation of the Project-Based Learning (PBL) model. The research benefits students, teachers, the school, and the Indonesian Language Teacher Working Group (MGMP Bahasa Indonesia). The study was conducted at SMP Negeri 4 Kendari with 32 students as subjects, consisting of 18 female and 14 male students. Based on the data obtained from three research cycles, the results showed that: (1) in the first cycle, 13 students (40.63%) achieved a score of ≥80, while in the second cycle, 31 students (96.88%) achieved a score of ≥80; (2) the teacher’s ability to manage the learning process improved from a total score of 120 (average 4, Good) in the first cycle to 132 (average 4.4, Good) in the second cycle; and (3) student activity during the learning process increased from a total score of 22 (73.33%, Fair) in the first cycle to 27 (90.00%, Very Good) in the second cycle. Based on these findings, it can be concluded that the Project-Based Learning (PBL) model effectively enhances students’ ability to read and write pantun in class VII-1 at SMP Negeri 4 Kendari.